2022
DOI: 10.1111/ctr.14799
|View full text |Cite
|
Sign up to set email alerts
|

Intensive ultrafiltration strategy restores kidney transplant candidacy for patients with echocardiographic evidence of pulmonary hypertension

Abstract: Introduction: Pulmonary hypertension (PH) is prevalent in those with end-stage kidney disease (ESKD) and poses a barrier to kidney transplant due to its association with poor outcomes. Studies examining these adverse outcomes are limited and often utilize echocardiographic measurements of pulmonary artery systolic pressure (PASP) instead of the gold standard right heart catheterization (RHC). We hypothesized that in ESKD patients deemed ineligible for kidney transplant because of an echocardiographic diagnosis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(86 reference statements)
0
2
0
Order By: Relevance
“…The reverse is also true, with patients with advanced renal failure and/ or dialysis-dependent developing TR, 51 likely in the setting of hypervolemia and RV failure. 52 Interestingly, one study of pulmonary hypertension in patients with end-stage renal failure showed that through aggressive ultrafiltration could lead to a significant reduction in pulmonary pressures, suggesting that hypervolemia is the major mechanism. 52 WHAT CAN WE LEARN FROM THIS ABOUT TREATMENT?…”
Section: Renal Functionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reverse is also true, with patients with advanced renal failure and/ or dialysis-dependent developing TR, 51 likely in the setting of hypervolemia and RV failure. 52 Interestingly, one study of pulmonary hypertension in patients with end-stage renal failure showed that through aggressive ultrafiltration could lead to a significant reduction in pulmonary pressures, suggesting that hypervolemia is the major mechanism. 52 WHAT CAN WE LEARN FROM THIS ABOUT TREATMENT?…”
Section: Renal Functionmentioning
confidence: 99%
“…52 Interestingly, one study of pulmonary hypertension in patients with end-stage renal failure showed that through aggressive ultrafiltration could lead to a significant reduction in pulmonary pressures, suggesting that hypervolemia is the major mechanism. 52 WHAT CAN WE LEARN FROM THIS ABOUT TREATMENT?…”
Section: Renal Functionmentioning
confidence: 99%